1994
DOI: 10.1111/j.1365-2052.1994.tb00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in two genes for B2 high sulfur proteins of wool

Abstract: SummaryVariation in the nucleotide sequence of the B2 high‐sulfur protein genes has not been reported previously. This paper reports 15 nucleotide substitutions in each of the genes for the B2A and B2C proteins and a length of polymorphism in the B2A gene which translates to the insertion/deletion of one 30‐nucleotide repeat sequence. Evidence is presented for gene conversion occurring within the B2 high‐sulfur multigene family. These DNA polymorphisms may account for some of the microheterogeneity observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 24 publications
1
64
0
1
Order By: Relevance
“…Although single nucleotide substitutions were observed between the KAP1.1 alleles, the major difference are that the A allele encodes one more decapeptide repeat than the B allele and two repeats more than the C allele (Rogers et al, 1994a Gender was found to have a significant effect on wool yield in both sire lines. In SL1, 24 months of age rams had a mean yield of 76.9 ± 0.40% which was higher (P = 0.013) than the ewes which had a mean yield of 75.5 ± 0.40%.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Although single nucleotide substitutions were observed between the KAP1.1 alleles, the major difference are that the A allele encodes one more decapeptide repeat than the B allele and two repeats more than the C allele (Rogers et al, 1994a Gender was found to have a significant effect on wool yield in both sire lines. In SL1, 24 months of age rams had a mean yield of 76.9 ± 0.40% which was higher (P = 0.013) than the ewes which had a mean yield of 75.5 ± 0.40%.…”
Section: Resultsmentioning
confidence: 87%
“…Numerous studies have described variation within both the KAP and KRT genes, including the work of Rogers et al (1994a); Parsons et al (1994a;1996); McLaren et al (1997) and Beh et al (2001). This genetic diversity could impact on wool fibre structure and hence variation in the genes, and proteins derived from them could therefore underpin variation in wool traits.…”
Section: Introductionmentioning
confidence: 99%
“…While length variation in the sequences encoding the cysteine-rich repeat segments has been described in KAP AE AA AD DD AC CC AC AB genes, it has only been reported previously in one family (KAP1) in sheep in which decapeptide length variation also occurs [10] and two families (KAP1 and KAP4) in humans [11,12]. The detection of length variation in the ovine KAP5-4 gene suggests that variation in the number of repeats coding for cysteine-rich segments may be a structural hallmark of some of the KAP genes.…”
Section: Resultsmentioning
confidence: 95%
“…KAP3.2 (together with KAP1.1, KAP1.3 and K33) have been mapped to ovine chromosome 1 (Figure 3.5). Variations in all of the three genes (KAP1.1, KAP1.3 and K33) have been previously associated with variation in wool traits (Itenge et al, 2009;Itenge et al, 2010;Rogers et al, 1994b). It is therefore suggested that sires that are heterozygous get investigated in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports associating variation in the KRT and KAP genes with variation in wool traits. Parsons et al (1994b) and Beh et al (2001) reported associations between variation in KAPs and mean fibre diameter in Merino sheep, while Rogers et al (1994b) reported association between staple strength in Romney sheep and the region spanning the KAP1.1/KAP1.3/K33 loci on ovine chromosome 11. Itenge et al (2009;2010) reported association between variation in the KAP1.1 gene with variation in yield.…”
Section: Previously Published Association Of Genetic Markers With Woomentioning
confidence: 99%